Environmental Safety and Economical Effectivness of the Water Well Rehabilitation - Gadaev A.N; Saidov S.S; Rajabov A.Kh; Juraev A.Kh; Ganieva D.U. (European Journal of Life Safety and Stability (2660-9630), 2022)
Long time operation of the water wells and poor groundwater quality is the result of the salt deposition. Also filter corrosion producs in the pores of the near-filter zone and on the surface of filters, which leads to decreasing in the productivity of wells. An efficient technology is proposed for processing and rehabilitation of flow rate of the artesian wells. This article is devoted to the environmental safety and economic feasibility study of this technology.